ANALISIS PENGGUNAAN OBAT PADA PASIEN PENYAKIT JANTUNG ISKEMIK DI RUMAH SAKIT Z KOTA JAMBI TAHUN 2023 - Athayyah Shabirah; Rasmala Dewi; Medi Andriani (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2024)
Ischemic Heart Disease is a condition that mainly occurs due to narrowing of the coronary arteries due to atherosclerosis, spasm, or a combination of both. The aim of this research is to determine the use of drugs which includes the right drug, the right indication, the right patient, the right dose and the right time interval for administering the drug in patients with Ischemic Heart Disease at Z Hospital, Jambi City in 2023. This research is a descriptive study with retrospective data collection. which searches the medical record data of patients in 2023 who meet the inclusion criteria. The results of this study found 115 patient medical record data that met the inclusion criteria with a percentage of drug accuracy of 99,13%, 100% correct indication, 87,83% correct patient, 100% correct dose, and only 33,91% correct time interval for drug.